The antioxidant and anti-inflammatory effects of Carica Papaya Linn. seeds extract on CCl4-induced liver injury in male rats - Nadia Z. Shaban; Sarah M. El-Kot; Olfat M. Awad; Afaf M. Hafez; Ghada M. Fouad (BMC, 2021)
Abstract Background Oxidative stress (OS) and inflammation are the central pathogenic events in liver diseases. In this study, the protective and therapeutic role of Carica Papaya Linn. seeds extract (SE) was evaluated against the hepatotoxicity induced by carbon tetrachloride (CCl4) in rats. Methods The air-dried papaya seeds were powdered and extracted with distilled water. The phytochemical ingredients, minerals, and antioxidant potentials were studied. For determination of the biological role of SE against hepatotoxicity induced by CCl4, five groups of adult male Sprague-Dawley rats were prepared (8 rats per each): C: control; SE: rats were administered with SE alone; CCl4: rats were injected subcutaneously with CCl4; SE-CCl4 group: rats were administered with SE orally for 2 weeks before and 8 weeks during CCl4 injection; SE-CCl4-SE group: Rats were administered with SE and CCl4 as mentioned in SE-CCl4 group with a prolonged administration with SE for 4 weeks after the stopping of CCl4 injection. Then, the markers of OS [lipid peroxidation (LP) and antioxidant parameters; glutathione (GSH), superoxide dismutase (SOD), glutathione-S-transferase (GST), glutathione peroxidase (GPx)], inflammation [nuclear factor (NF)-κB, tumor necrosis factor (TNF)-α, interleukin (IL)-6], fibrosis [transforming growth factor (TGF)-β], apoptosis [tumor suppressor gene (p53)], liver and kidney functions beside liver histopathology were determined. Results The phytochemical analyses revealed that SE contains different concentrations of phenolics, flavonoids, terpenoids, and minerals so it has potent antioxidant activities. Therefore, the treatment with SE pre, during, and/or after CCl4 administration attenuated the OS induced by CCl4 where the LP was reduced, but the antioxidants (GSH, SOD, GST, and GPx) were increased. Additionally, these treatments reduced the inflammation, fibrosis, and apoptosis induced by CCl4, since the levels of NF-κB, TNF-α, IL-6, TGF-β, and p53 were declined. Accordingly, liver and kidney functions were improved. These results were confirmed by the histopathological results. Conclusions SE has protective and treatment roles against hepatotoxicity caused by CCl4 administration through the reduction of OS, inflammation, fibrosis, and apoptosis induced by CCl4 and its metabolites in the liver tissues. Administration of SE for healthy rats for 12 weeks had no adverse effects. Thus, SE can be utilized in pharmacological tools as anti-hepatotoxicity.